การมีส่วนร่วมของผู้ดูแลชาวกะเหรี่ยงในการดูแลเด็กป่วยที่ติดเชื้อทางเดินหายใจที่เข้ารับการรักษาในโรงพยาบาลชุมชน - ศรันย์ ปองนิมิตพร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Respiratory tract infections have been one of the major causes for Karen children being admitted to community hospitals. This descriptive research aimed to study actual and preferred parent participation in caring for children with respiratory tract infections, among Karen caregivers in community hospitals. The purpose of this study was also to make comparisons. The sample of the study were Karen caregivers of children with respiratory tract infections, from newborn to 5 years old, admitted in community hospitals in Chiang Mai and Mae Hong Son provinces during January to March, 2014. Purposive sampling was employed, and 140 Karen caregivers were selected to participate in this study. The Parent Participation Scale of Schepp, translated into Thai by Chaichana et al (2002) was used, and then translated into Karen language. The reliability was tested using Cronbach's alpha Coefficient. The confidence of the actual and preferred participation in caring for children were .87 and .88 respectively. Data were analyzed using descriptive statistics, paired t-test, Wilcoxon Matched Pair Signed Ranks test, and content analysis. The study found that the Karen caregivers had a score of preferred at a high level (xˉ = 76.87, SD = 0.97). When considering each aspect, preferred participation in routine care, technical care and information sharing were also at a high level (xˉ = 20.53, SD = 2.85; xˉ = 27.06, SD = 3.29; xˉ = 12.64, SD = 3.36, respectively). Moreover, preferred participation in decision-making was at moderate levels (xˉ = 16.64, SD = 5.01). The caregivers had a mean score of actual participation at high level (xˉ = 75.86, SD = 11.73). When considering each aspect, actual participation in routine care, technical care and information sharing were also at a high level (xˉ = 20.51, SD= 2.68; xˉ = 26.59, SD= 3.53; xˉ = 12.56, SD= 3.52, respectively). Moreover, their actual participation in decision-making at moderate level (xˉ = 16.19, SD = 5.14). There were no significant differences between actual participation and preferred participation in routine care, information sharing, and decision-making. However, there was statistically significant actual participation, and preferred participation in technical care at the level of .05 Data from interviews revealed that Karen caregivers participated in routine caregiving since they were aware of their responsibilities in their constantly played role as parents. Moreover, the hospital's policy was supportive and the caregivers preferred to participate in 1) routine care: they expressed their needs to act according to their daily activities and their own beliefs, 2) technical care: they desired to practice under the supervision or guidance of staffs as well as to receive their assistance during procedures, and 3) information sharing and decision-making: a translator was needed, and caregivers’ participation in every decision regarding treatment for their children was required. The results of this study suggest that nurses should realize the importance of caregivers’ participation and their needs to participate in child care. Providing a translator to support the information exchange between caregivers and nursing staffs was required. Moreover, the results could be used to mobilize Karen caregiver’s participation in providing effective care for children with respiratory tract infections admitted to community hospitals.